MANAJEMEN PENINGKATAN PROFESIONALISME GURU DI MTS AL-AMANAH PASEH - Jujuniarti, Imas; Rukajat, Ajat; Sopiyan, Iyan (Jurnal Pendidikan Indonesia : Teori, Penelitian, dan Inovasi, 2021)
This research aims to answer several problem formulations, including: 1). What is the Definition of Management to Improve Teacher Professionalism? 2). How to Improve Teacher Professionalism Management at MTs Al-amanah Paseh Regency, 3). What are the inhibiting and supporting factors in implementing management in increasing teacher professionalism? 4). How Management Steps Improve Teacher Professionalism. This research was conducted using qualitative research methods with the aim of describing or describing phenomena as they exist at the research location. The data collected in the research is through careful observation, interviews and documentation, so that the research results are arranged systematically, the researcher's steps in analyzing the data are first, with the main points and focusing on the important things, second, presenting the data properly. carried out in the form of short descriptions, and the like. Third, draw conclusions to answer the problem formulated from the start. The results and data analysis can be concluded that (1) Management of increasing teacher professionalism is a way or technique to increase educational competitiveness both in quantity and quality of students towards their environment. To increase teacher professionalism, (2) Implementation of increasing teacher professionalism management by providing good student development, namely with coaching by teachers and teachers there will be supervision from the school principal, (3) inhibiting and driving factors in the implementation of management to increase teacher professionalism are always there including internal and external obstacles from both the school and outside because if from the school there is jealousy from other teachers who not included in training or training, there are still many teachers/instructors at MTs Al-amanah who are still constrained by teaching time because there are still many teachers who are not still in the sense of not being able to teach in one place. while the supporting factors are self-awareness, motivation, encouragement from the school principal, and supporting infrastructure in the teaching and learning process. (4) Management efforts to increase teacher professionalism include programs to increase teacher education qualifications, equalization and certification, educational supervision, MGMP empowerment, training, reading, participating, attending training, actively organizing and fostering collaboration with colleaguesABSTRAKPenelitian ini bertujuan untuk menjawab beberapa rumusan masalah, diantaranya: 1). Apa Pengertian Manajemen untuk Meningkatkan Profesionalisme Guru? 2). Bagaimana Meningkatkan Manajemen Profesionalisme Guru di MTs Al-amanah Kabupaten Paseh, 3). Apa saja faktor penghambat dan pendukung dalam penerapan manajemen dalam meningkatkan profesionalisme guru? 4). Bagaimana Langkah-Langkah Manajemen Meningkatkan Profesionalisme Guru. Penelitian ini dilakukan dengan menggunakan metode penelitian kualitatif dengan tujuan untuk mendeskripsikan atau mendeskripsikan fenomena sebagaimana adanya di lokasi penelitian. Data yang dikumpulkan dalam penelitian adalah melalui observasi, wawancara, dan dokumentasi yang cermat, sehingga hasil penelitian tersusun secara sistematis, langkah-langkah peneliti dalam menganalisis data adalah pertama, dengan pokok-pokok dan pemusatan pada hal-hal penting, kedua, penyajian data yang dilakukan dalam berupa uraian singkat, dan sejenisnya. Ketiga, menarik kesimpulan untuk menjawab masalah yang dirumuskan sejak awal. Hasil dan analisis data dapat disimpulkan bahwa (1) Manajemen peningkatan profesionalisme guru merupakan cara atau teknik untuk meningkatkan daya saing pendidikan baik kuantitas maupun kualitas siswa terhadap lingkungannya Untuk meningkatkan profesionalisme guru, (2) Pelaksanaan peningkatan manajemen guru profesionalisme dengan pembinaan pembinaan siswa yang baik yaitu dengan pembinaan oleh guru dan guru akan ada pengawasan dari kepala sekolah, (3) faktor penghambat dan pendorong dalam pelaksanaan manajemen peningkatan profesionalisme guru selalu ada termasuk kendala internal maupun eksternal baik dari pihak sekolah atau luar karena jika dari pihak sekolah ada kecemburuan dari guru lain yang tidak diikutkan diklat atau diklat, masih banyak guru/instruktur di MTs Al-amanah masih terkendala waktu mengajar karena masih banyak guru yang tidak masih dalam arti tidak ada k mengajar di satu tempat. sedangkan faktor pendukungnya adalah kesadaran diri, motivasi, dorongan dari kepala sekolah, dan sarana prasarana pendukung dalam proses belajar mengajar. (4) Upaya pengelolaan untuk meningkatkan profesionalisme guru meliputi program peningkatan kualifikasi pendidikan guru, pemerataan dan sertifikasi, supervisi pendidikan, pemberdayaan MGMP, pelatihan, membaca, berpartisipasi, mengikuti pelatihan, aktif berorganisasi dan membina kerjasama dengan rekan sejawat